Examining the Energy Envelope and Associated Symptom Patterns in ME/CFS: Does Coping Matter? - Brown, Abigail A. (2013)
OBJECTIVE/HYPOTHESIS: The objective of this study was to examine sub-types of individuals with Myalgic Encephalomyelitis/chronic fatigue syndrome (ME/CFS) based upon variables that are theoretically associated with the Energy Envelope Theory (EET), and to examine the role of coping strategies in explaining the differences found between the subtypes. METHODS: Cluster analysis was used. Grouping variables included physical functioning, post-exertional malaise severity, and the extent to which an individual was outside of the EE. These clusters were evaluated using discriminant function analysis to determine whether they could be differentiated based on coping styles. RESULTS: Cluster analysis identified three groups. Clusters 1 and 2 were consistent with the EET. However, Cluster 3 was characterized by patients with the most impairment, but they were to a lesser extent exceeding their EE. Coping strategies explained a small percentage (10%) of the variance in differentiating the clusters. DISCUSSION: Energy maintenance may be associated with improved functioning and less severe symptoms for some. However, patients in Cluster 3 were closer to remaining within their EE and also used higher levels of adaptive coping, but were more impaired than Cluster 2. This suggests that adaptive coping strategies were not associated with improved health, as members of Cluster 3 were severely limited in functioning.